Influence of niobium pentoxide addition on the properties of glass ionomer cements - Isadora Martini Garcia; Vicente Castelo Branco Leitune; Gabriela De Souza Balbinot; Susana Maria Werner Samuel; Fabrício Mezzomo Collares (Taylor & Francis Group, 2016)
Objective: To determine the influence of niobium pentoxide (Nb2O5) addition on the physical and chemical properties of glass ionomer cements (GICs). Materials and methods: Five, 10 or 20 wt.% of Nb2O5 were incorporated into commercial GICs (Maxxion R, Vitro Molar, Vitro Fil R) and one group of each GIC remained without Nb2O5 (control groups). The GICs were evaluated by Knoop hardness, compressive strength, acid erosion, particle size and radiopacity. Data were analyzed by two-way ANOVA followed by Tukey's test. Results: The addition of 10% and 20% reduced the microhardness of two GICs (p < .05). Compressive strength showed no difference among groups (p > .05). Nb2O5 did not influence Maxxion R and Vitro Fil R regarding the acid erosion test (p > .05). Vitro Molar increased its acid erosion with 10% of Nb2O5 (p < .05). Maxxion R presented 15.78 μm, while Vitro Molar and Vitro Fil R showed 5.14 μm and 6.18 μm, respectively. As the Nb2O5 concentration increased, the radiopacity increased for all groups. Vitro Molar and Vitro Fil R did not present significant difference to at least 1 mm aluminum (p > .05). Conclusion: The addition of 5 wt.% Nb2O5 did not affect the tested physical and chemical properties of the GICs and improved the radiopacity of one of the cements. These materials are therefore suitable for further testing of biomimetic remineralization properties.